EFFECT OF BISPHENOL- A ON ANTIOXIDANT ENZYMES, REPRODUCTIVE HORMONES AND APOPTOTIC CHANGES IN PLACETAL AND UTERINE TISSUES OF ALBINO RAT - T.GEETHARATHAN; P. JOSTHNA (International Journal of Pharma and Bio Sciences, 2016)
Bisphenol-A is a widely used industrial plasticizer with known estrogenic properties. It is omnipresent in the environment and widely distributed and unavoidable. It accumulates in pregnant adult females and its continued exposure during gestation is likely to have an impact on the development of the fetus. Bisphenol- A was administered orally from 8th day of gestation to 15th day in a dose of (50 mg and 500mg/kg, b.wt) during the same period of gestation. The aim of this study was to evaluate the anti oxidant enzyme analysis, reproductive hormones and apoptotical changes in placenta and uterine tissues. In this study, we observed imbalance of antioxidant enzymes in serum, altered the expression levels of reproductive hormones, changes in apoptotic proteins that is proapoptotic protein caspase-3 was significantly increased in placental and uterine tissues of BPA treated rats.